PARADOKS MITOLOGI HINDU DI JAWA (Relevansinya sebagai Tutur dan Batur Umat Hindu) - Miswanto Miswanto (Jnanasidanta, 2020)
Hindu mythology in Java developed since the entry of Hindu civilization into Indonesia. Javanese people believe these myths as a local wisdom that must be maintained. Although there are some Javanese people who doubt it, the existence of Hindu mythology in Java is maintained and even becomes a source of inspiration in their social and religious life. This phenomenon makes Hindu mythology in Java as a paradox, whose existence is still needed even though some people doubt it. Up to now the values contained in Hindu mythology are integrated in the Javanese way of life (tutur) of the people and are rooted in the breath of their spiritual life and make them survive (batur) as Javanese people who ‘njawani’. For Hindus on Java, Hindu mythology has also become one of the mediums of teaching religion, especially if it is related to its origins from Itihāsa and Purāṇa.